Methods to Assess the Protective Efficacy of Emollients against Climatic and Chemical Aggressors - Romain Roure; Marion Lanctin; Virginie Nollent; Christiane Bertin (Hindawi Limited, 2012)
Exposure to harsh environmental conditions, such as cold and dry climate and chemicals can have an abrasive effect on skin. Skin care products containing ingredients that avert these noxious effects by reinforcement of the barrier function can be tested using in vivo models. The objective is to use in vivo models to assess the efficacy of emollients in protecting skin against climatic and chemical insults. A first model used a stream of cooled air to mimic cold wind. A second used sodium lauryl sulfate (SLS) under patch as chemical aggressor. In the model with simulated wind exposure, the untreated exposed area had a significant decrease in hydration. In contrast, application of an emollient caused a significant increase in hydration that was maintained after wind exposure. In the second model with SLS exposure, application of a barrier cream before SLS patch significantly reduced the dehydrating effect of SLS with a significant difference in variation between both areas. Application of the cream reduced TEWL, indicative of a physical reinforcement of the skin barrier. The two presented test methods, done under standardized conditions, can be used for evaluation of protective effect of emollient, by reinforcing the barrier function against experimentally induced skin dehydration.